IET Irish Signals and Systems Conference (ISSC 2008) 2008
DOI: 10.1049/cp:20080632
|View full text |Cite
|
Sign up to set email alerts
|

Structural division procedure for efficient IC analysis

Abstract: Follow this and additional works at:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It only allows actions upon transition into a state. This concept is useful in cases where a number of finite state machines are required to work together, and when it is convenient to consider a purely combinatorial part as a form of FSM to suit the design tools (Brutscheck, 2008).…”
Section: Discussion In String Matchingmentioning
confidence: 99%
“…It only allows actions upon transition into a state. This concept is useful in cases where a number of finite state machines are required to work together, and when it is convenient to consider a purely combinatorial part as a form of FSM to suit the design tools (Brutscheck, 2008).…”
Section: Discussion In String Matchingmentioning
confidence: 99%
“…It only allows actions upon transition into a state. This concept is useful in cases where a number of finite state machines are required to work together, and when it is convenient to consider a purely combinatorial part as a form of FSM to suit the design tools (Brutscheck, 2008). * There are other sets of semantics available to represent state machines.…”
Section: How Does It Do It?mentioning
confidence: 99%
“…The determination of pin types is the first analysis step which was described in detail in [6]. This is followed by a preliminary investigation of the IC under test which results in combinatorial, sequential linear or sequential nonlinear behaviour as described in [7]. Here, it was demonstrated that a real IC can be abstracted using the model of automaton [8].…”
Section: Introductionmentioning
confidence: 99%